Salesperson's tenure: a comparative study from three consumer sector industries - Zain, Osman M.; Jan, Muhammad Tahir (2012)

(untitled)
Salesperson’s tenure is a major issue for companies especially in today’s era of high competition. High rates of employees turnover is reported to impact organisational productivity and competitiveness. The present study aims to identify and test those factors which are playing an important role in salesmanship career tenure. Moreover, it also aims to find out any equivalence or non-equivalence in the antecedents of salespersons’ tenure across three different industries, namely, automobile, insurance, and multi-level-marketing (MLM). For this purpose a self-administered questionnaire was designed and distributed among 600 salespeople working in the aforementioned three sectors. A total of 395 usable questionnaires were finally selected for data analysis. The data analysis was conducted using SPSS and AMOS software programme packages for windows. First of all the data was screened for any missing values, outliers, and normality. After screening of the data, descriptive analysis was undertaken to gain insight into the acquired data. Descriptive statistical analyses revealed that majority of the respondent were males. Further it was exposed in the analyses that most of the respondents were married (57.2%) and was from the age group of 25 to 34. Around thirty-nine per cent of the respondents had a minimum of certificate or diploma level education and were Malays. After descriptive statistical analysis, exploratory factor analysis was conducted to extract the number of factors and their subsequent items. These extracted factors and items were then confirmed using confirmatory factor analysis. A total of five factors were extracted and confirmed during exploratory and confirmatory factor analysis. Structural equation modelling (SEM) was then used to examine the variables and the fitness of proposed model. We found a significant positive impact of intrinsic motivation on job satisfaction and organisational commitment. Similarly, we also found the impact of organisational commitment on employee productivity and tenure, and the impact of employee productivity on tenure. Finally, structural invariance tests were conducted in order to examine structural invariance of the baseline model across three different consumer sector industries. The results revealed that the baseline model is non-invariant across automobile, insurance, and MLM. Suggestions for further research, using the same model, were given based on our findings. The findings of this study have a major implication for marketing organisations and more specifically for recruitment agencies.